2021
DOI: 10.1029/2021wr029717
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Roughness Spacing and Size on the Lateral Deflection of Bedload Particles

Abstract: Bedrock erosion can be divided into the vertical incision and lateral erosion. Vertical incision deepens the valleys, steepens the hillslopes, and is thus a primary process for landscapes to respond to spatial-temporal variations of tectonic deformation (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
(130 reference statements)
0
4
0
Order By: Relevance
“…The sideward deflection length d is expected to vary in space and time and likely depends on channel hydraulics, roughness, and sediment supply (Beer et al, 2017;Fuller et al, 2016;He et al, 2021;Li et al, 2020;Turowski, 2018Turowski, , 2020. However, for simplicity, the current analysis assumes that d is constant and uniform.…”
Section: Influence Of Boulders On Bedrock Erosionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sideward deflection length d is expected to vary in space and time and likely depends on channel hydraulics, roughness, and sediment supply (Beer et al, 2017;Fuller et al, 2016;He et al, 2021;Li et al, 2020;Turowski, 2018Turowski, , 2020. However, for simplicity, the current analysis assumes that d is constant and uniform.…”
Section: Influence Of Boulders On Bedrock Erosionmentioning
confidence: 99%
“…A field study in a bedrock channel gorge in Switzerland showed that wall erosion increases in proximity to roughness elements (Beer et al., 2017). Although recent studies proposed a positive relationship between lateral erosion and channel roughness (Fuller et al., 2016; He et al., 2021; Li et al., 2020; Turowski, 2018), the precise nature of this relationship and its relation to large boulders remains to be explored (Turowski, 2020).…”
Section: Background For Large Boulder Control On Channel Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…In Chen et al (2019)'s study, different sizes of streambed sediment were scanned and reconstructed based on structure-from-motion (SfM) photogrammetry, and they discovered that the stream flow resistance was mainly controlled by the standard deviation of the bed elevation normalized by water depth. As for these aquatic organisms, the species, sizes, densities and distribution may play important roles in flow resistance (Ghisalberti, 2009;Wang et al, 2010;Mossa et al, 2017;He et al, 2021). Therefore, some hydraulic models incorporate the geometric features of the roughness elements to increase the prediction of flow resistance (D'Ippolito et al, 2021).…”
Section: Introductionmentioning
confidence: 99%